Adopting workload-based staffing norms at public sector health facilities in Bangladesh: evidence from two districts - Md Nuruzzaman; Tomas Zapata; Valeria De Oliveira Cruz; Sabina Alam; Samiun Nazrin Bente Kamal Tune; Taufique Joarder (BMC, 2022)
Abstract Background Bangladesh's Health system is characterized by severe shortage and unequitable distribution of the formally trained health workforce. In this context, government of Bangladesh uses fixed staffing norms for its health facilities. These norms do not always reflect the actual requirement in reality. This study was conducted in public sector health facilities in two selected districts to assess the existing staffing norms with the purpose of adopting better norms and a more efficient utilization of the existing workforce. Methods To carry out this assessment, WHO's Workload Indicators of Staffing Need (WISN) method was applied. Selection of the two districts out of 64 and a total of 24 health facilities were made in consultation with the formally established steering committee of the Ministry of Health. Health facilities, which were performing well in serving the patients during 2016-2017, were selected. This assessment examined staffing requirement of 20 staff categories. Results Based on the computer-generated WISN results, most of the staff categories were found to have a workload pressure of Very High (seven out of 20 staff categories), followed by Extremely High (five staff categories). Two staff categories had high, three had moderately high, two normal, and one low workload. Nurses were found to be predominantly occupied with support activities (50-60% of working time), instead of actual nursing care. Regarding vacancy, if all the vacant posts were filled, understandably, the workload would reduce, but not yet sufficient to meet the existing staff requirements such as consultants, general physicians and nurses at the district and sub-district/upazila-based hospitals. Conclusion The existing staffing norms fall short of the WISN staffing requirement. The results provide evidence to prompt a revisit of the staffing policies and adopt workload-based norms. This can be supplemented by reviewing the scope of practice of the staff categories in their respective health facilities. In the short term, government might consider redistributing existing workforce as per workload. In the long term, revision of staffing norms is needed to provide quality health services for all.